2016
DOI: 10.1177/0954405416673684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting fluid on precision machined surface integrity of heat-resistant stainless steel

Abstract: The machined surface integrity of blades is of utmost importance in the power equipment manufacturing industry. Recently, many blade accidents have been attributable to the misuse of cutting fluids that were necessary in the actual machining of difficult-to-cut materials, but the effect of the cutting fluid on surface integrity and service performance has been persistently neglected. In this article, an investigation into the effect of cutting fluids on the surface quality of a typical blade material was under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The results show significant corrosion of Fe-based superalloy after prolonged Molecules 2023, 28, 3648 2 of 17 exposure to cutting fluid. Yan P. et al [8] studied the effect of cutting fluid on stainless steel material. The results indicated that corrosion occurred related to the local loss of elemental chromium by using cutting fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The results show significant corrosion of Fe-based superalloy after prolonged Molecules 2023, 28, 3648 2 of 17 exposure to cutting fluid. Yan P. et al [8] studied the effect of cutting fluid on stainless steel material. The results indicated that corrosion occurred related to the local loss of elemental chromium by using cutting fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the actual machining process in industry, two universal micro-emulsified cutting fluids, denoted as E709 (Master brand, TRIM ® E709 soluble oil) and Blasocut (Blaser Brand, Blasocut 4000 strong mineral oil base high performance cutting fluid), were selected and researched. In order to make sure the cooling, lubricating and corrosion properties of these two cutting fluids, the physical and chemical properties, including viscosity, friction coefficient, surface tension, cooling performance, and pH, were examined, similar to the previous research [ 28 ]. Each test was repeated three times, and then, the average was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of the cutting process on the surface integrity of the finished part have gained significant interest during latter years. 2125 Several studies have been published on the size and influence of h 1 min for different machining operations. Yuan et al 13 conclude that the tool edge radius r β has a major influence on the size of h 1 min .…”
Section: Minimum Chip Thickness H1minmentioning
confidence: 99%